Enhancing plant defense using rhizobacteria in processing tomatoes: a bioprospecting approach to overcoming Early Blight and Alternaria toxins - Bellotti, Gabriele; Guerrieri, Maria Chiara; Giorni, Paola; Bulla, Giulia; Fiorini, Andrea; Bertuzzi, Terenzio; Antinori, Maria Elena; Puglisi, Edoardo (Frontiers in Microbiology, 2023)
Plant growth-promoting rhizobacteria (PGPR) with antagonistic activity toward plant pathogenic fungi are valuable candidates for the development of novel plant protection products based on biocontrol activity. The very first step in the formulation of such products is to screen the potential effectiveness of the selected microorganism(s). In this study, non-pathogenic rhizobacteria were isolated from the rhizosphere of tomato plants and evaluated for their biocontrol activity against three species of mycotoxin-producing Alternaria. The assessment of their biocontrol potential involved investigating both fungal biomass and Alternaria toxin reduction. A ranking system developed allowed for the identification of the 12 best-performing strains among the initial 85 isolates. Several rhizobacteria showed a significant reduction in fungal biomass (up to 76%) and/or mycotoxin production (up to 99.7%). Moreover, the same isolates also demonstrated plant growth-promoting (PGP) traits such as siderophore or IAA production, inorganic phosphate solubilization, and nitrogen fixation, confirming the multifaceted properties of PGPRs. Bacillus species, particularly B. amyloliquefaciens and two strains of B. subtilis, showed the highest efficacy in reducing fungal biomass and were also effective in lowering mycotoxin production. Isolates such as Enterobacter ludwigii, Enterobacter asburiae, Serratia nematodiphila, Pantoea agglomerans, and Kosakonia cowanii showed moderate efficacy. Results suggest that by leveraging the diverse capabilities of different microbial strains, a consortium-based approach would provide a broader spectrum of effectiveness, thereby signaling a more encouraging resolution for sustainable agriculture and addressing the multifaceted nature of crop-related biotic challenges.